Pupils' perceptions of Key Stage 2 to Key Stage 3 transition in modern foreign languages. Issue 1 (1st January 2019) - Chambers, Gary
Abstract : Modern foreign languages (MFL) are now established on the timetable of English primary schools. This study accesses the views of the pupils on the experience of learning this relatively new subject and of making the transition to secondary school languages classes. By means of semi-structured interviews with the same sample of 18 pupils in Year 6 (age 10 or 11) and again in Year 7 (age 11 or 12), we learn that, whilst they enjoy languages at primary school, the enjoyment is all the greater in secondary school. As pupils look back from secondary school on the primary school experience, they identify that they want to feel challenged by more, harder work and to know that they are progressing and achieving. They want to be taught by teachers with MFL competence and appropriate training. Limited resources mean that MFL learning and teaching and transitional arrangements are not perfect. The insights which the pupils provide raise questions about how schools might be enabled by policy-makers to address the imperfections.